PERAN GURU DALAM MENANAMKAN NILAI DISIPLIN PADA ANAK USIA DINI DI TK AISYIYAH BUSTANUL ATHFAL DAYA - Rusliana, Faradillah; Rusmayadi, Rusmayadi; Amal, Azizah (STKIP PGRI Situbondo, 2025)
This study aims to determine the role of teachers in instilling values of discipline in children in Group B of the Aisyiyah Bustanul Athfal Kindergarten. Data collection was carried out using qualitative research methods through observation, interviews, and documentation. This study was conducted in Group B of the Aisyiyah Bustanul Athfal Kindergarten with four teachers as research subjects. This study produced three main findings, namely the role of teachers in instilling values of discipline in children by instilling a sense of responsibility and the habit of disciplined behavior, the efforts of teachers in instilling values of discipline in children, namely accustoming children to be disciplined in terms of managing their time for studying and playing, as well as setting an example through the behavior of the Prophet Muhammad, andd dthe challenges dfaced dby dteachers din dinstilling discipline dvalues in children, namely differences in educational approaches between home and school, and insufficient parental attention toward their children.